Emerging technologies and sports events: Innovative information and communication solutions - Petrovic, L. T.; Milovanovic, D.; Desbordes, M. (Sport, Business and Management, 2015)
The purpose of this paper is to review the development and potential applications of emerging information and communication technologies (ICTs) in sports. The case studies are presented in details: computer system for tracking and visualisation in TV broadcasting and players/teams performance analysis in football. The paper concludes with the authors` opinion that future implementation of digital technologies, in the first instance, goal-line technologies, to support accurate, practical and reliable decision making in sports is highly needed and represent a basis for further increase in the commercial value of the pre-eminent global sport.